Perception on Learning English Conversation through Zoom Meeting - Elga N. Lamadenreng; Nurmin Samola; Nihta V. F. Liando (English Education Department, 2024)
This study aims to find out the perceptions of teachers and students in the process of learning English conversation through Zoom Meeting The method used in this study was quantitative method Data collection in this study was carried out using a survey technique by distributing questionnaires The researcher used Google form as a data collection tool The type of questionnaire was closed questionnaire The questionnaires were distributed to 7 English teachers and 36 students The results of the data analysis stated that teachers and students were greatly helped by learning English conversation through Zoom Meeting in learning activities Teachers and students also have supporting devices and the government provides assistance to support the process of learning English conversation through Zoom Meetings However many teachers have disagreed that they have never experienced obstacles in the process of learning English conversation It is suggested for teachers to help students improve their learning English conversation through online application in this case Zoom meeting Students could learn more about the material provided by teachers through Zoom Meeting For researchers it could be as a reference in conducting studies regarding perception on learning English conversation < p>